Fundus Autofluorescence Imaging in Multifocal Choroiditis: Beyond the Spots. (October 2014) - Kramer, Michal; Priel, Ethan
Abstract Purpose: To describe fundus autofluorescence (FAF) imaging and its correlation to spectral-domain optical coherence tomography (SD-OCT) in retinal areas that appear clinically noninvolved in patients with multifocal choroiditis/punctate inner choroidopathy (MFC/PIC). Methods: Six patients with MFC or PIC were evaluated during the disease course with multimodal imaging, which included fluorescein angiography, FAF imaging, indocyanine green angiography, and SD-OCT. Results: Five patients had acute and/or scarred chorioretinal spots at presentation. Five patients had choroidal neovascularization. FAF imaging in all patients disclosed diffuse peripapillary and/or posterior-pole hyperautofluorescent plaques in areas that appeared clinically to be noninvolved. Corresponding SD-OCT scans revealed severe disruption of the inner segment/outer segment junction. Findings resolved with corticosteroid treatment Conclusions: FAF imaging of patients with MFC/PIC reveals extensive pathology beyond the clinically apparent spots. FAF findings highlight the areas of corresponding anatomic disruption of the photoreceptor–retinal pigment epithelium complex.